Design Principles for Cationic, Astrocyte‐Targeted Probes. (23rd January 2019) - Preston, Alyssa N.; Farr, Joshua D.; Tan, Kevin C.; Cervasio, Danielle A.; Butkus, Lauren R.; Laughlin, Scott T.
Abstract: The brain's astrocytes play key roles in normal and pathological brain processes. Targeting small molecules to astrocytes in the presence of the many other cell types in the brain will provide useful tools for their visualization and manipulation. Herein, we explore the functional consequences of synthetic modifications to a recently described astrocyte marker composed of a bright rhodamine‐based fluorophore and an astrocyte‐targeting moiety. We altered the nature of the targeting moiety to probe the dependence of astrocyte targeting on hydrophobicity, charge, and p K a when exposed to astrocytes and neurons isolated from the mouse cortex. We found that an overall molecular charge of +2 and a targeting moiety with a heterocyclic aromatic amine are important requirements for specific and robust astrocyte labeling. These results provide a basis for engineering astrocyte‐targeted molecular tools with unique properties, including metabolite sensing or optogenetic control. Abstract : Having a plus is a plus : The structural requirements of organic cation transporter–targeting moieties are explored for use as astrocyte‐specific probes. Targeting moieties with a permanent, positive charge and heterocyclic aromatic amine were found to robustly label primary cultures of astrocytes when attached to a bright rhodamine‐based fluorophore.